The Relationship between the Intensity of Social Media Use and Eating Behavior among Nursing Students - Aulia Wulandari; Akhmad Faozi; Amanda Puspanditaning Sejati (Inspirasi Foundation, 2026)
Introduction: The quick development of social media has become an important aspect of students’ lives, including its influence on lifestyle formation and eating behavior patterns. Extensive exposure to visual content, food-related posts, digital advertisements, and online social interactions has the potential to affect tendencies toward uncontrolled eating and emotional eating. Objective: The purpose of this study is to ascertain how nursing students at the Indonesia university of education, Sumedang Campus, use social media in relation to their eating habits. Methods: A quantitative method with a cross-sectional design was used, which included 215 respondents selected through probability sampling. Data were collected using the Social Networking Time Use Scale (SONTUS) to measure social media use intensity and the Dutch Eating Behavior Questionnaire (DEBQ) to assess eating behaviors. Data analysis was conducted using the Chi-Square test. Result: The results indicate a significant relationship between social media use intensity and students’ eating behavior (p-value < 0.05). These findings suggest that higher social media use intensity may influence eating patterns, including tendencies toward uncontrolled eating, emotional eating, and eating triggered by digital environmental cues. Conclusion: This study provides a foundation for developing digital literacy programs and promotive interventions aimed at encouraging healthy eating behaviors among university students.